ANALISIS PERLINDUNGAN HUKUM TERHADAP KONSUMEN DAN TANGGUNG JAWAB PT. PLN (PERSERO) DALAM PENCATATAN KWH METER LISTRIK DI KOTA KUPANG DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Seseli, Yunita Berlian; Jacob, Yossie M Y; Kaesmetan, Rini Marselin; Ndolu, Juliana S (Petitum Law Journal, 2025)
Indonesia is a state governed by law, prioritizing legal principles in all aspects of national life. One effort to uphold this principle is the development of legal frameworks to ensure justice, legal certainty, order, and a law-conscious society. Upholding the rule of law and justice is rooted in Pancasila and the 1945 Constitution of the Republic of Indonesia (hereinafter referred to as UUD 1945), which emphasizes human rights and guarantees equality for all citizens before the law and government without exception. Legal protection for consumers is a fundamental issue in public services, including electricity provision. This study focuses on the recording of kilowatt-hours meters by PT. PLN (Persero) in Kupang City, which often experiences inaccuracies that may disadvantage consumers. This study employs an empirical juridical approach, with primary data obtained through interviews and observations, and secondary data gathered from literature reviews. The findings reveal that (1) inaccuracies in kilowatt-hours meter recording frequently occur due to human errors, device malfunctions, and system weaknesses, causing financial losses to consumers. (2) PT. PLN is responsible for correcting errors, providing compensation, and improving the recording system. Recommendations include enhancing recording accuracy, replacing defective devices, and educating consumers about their rights. Implementing more effective legal protection is expected to increase consumer trust in electricity services.